(untitled) (Bangladesh Journal of Urology, 2023)
Background: In medical science specially in surgery Halsteadian principle, which includes “see one, do one, teach one” has shifted to the paradigm of “See several, simulate many, do one perfectly”. Repeated practice in simulators has a great role to be familiar with the procedures before going to practice in practical field. In Bangladesh access to a simulator system is difficult due to less accessibility and availability. Though Bangladesh is a developing country and unable to spend more money for simulator based educational system homemade simulators. Objective: To evaluate feasibility and appropriateness of homemade simulations in urological training system. Method: This observational study was conducted in the Department of Urology, NIKDU and in a private hospital from February 2019 to October 2019. Sample was collected by purposively from Urology residents and young urologist of NIKDU. Total participants were twenty six (26). Urology residents and young urologists who were interested to take part in simulation training and survey are included in this study. A questionnaire was prepared. A good number of residents and young urologists were present in the study. All of them performed procedures in TURP simulator, URS simulator, PCNL simulator and laparoscopy simulator. The questionnaire was supplied to the residents and young urologists after the procedures. All papers were collected and results were calculated. Results: During the study out of 26 participants, 20 (76.9%) participants expressed no incorporated simulation training program in residency curriculum and 23 (88.4%) participants have no access to a simulation education centre. 20 (76.92%) participants think that there is a role for a standardized simulator training curriculum during your residency period. 25(96%) participants agreed that simulators would improve operating room performance. 16 (61.5%) participants think cost is a limiting factors and 10(38.46%) participants didn’t agree that cost is a limiting factor. 19 (73.08%) participants think that simulation practice can reduce patients risk & complications during surgery while 7 (26.92%) think not like that. 18 (69.23%) participants thinks the necessity to improve the quality of these homemade simulators to further improve the quality of simulator training program, while 8 participants thinks these simulators are sufficient for training. 92.31% participants believe it is necessary to include the simulation training program in urology residency. Most of the participants (96.15%) thinks that these cost effective homemade simulators are helpful in improving surgical skills. Conclusion: In the early period of one’s urological career, simulators would help shorten the learning curve by enabling repetitions and revisions. Homemade simulators could be a solution to meet the current needs in the field of urology in our country. Bangladesh J. Urol. 2023; 26(2): 96-103